Tecnologias da informação e da comunicação no ensino-aprendizagem - (:unkn) unknown (Universidade Federal do Pampa, 2023)
Since the 1990s, the world has undergone major advances, particularly the accelerated development of technology, which has brought significant changes in the economy, politics, communication, and interpersonal relationships. Communication has become increasingly relevant in social interactions, and new technologies allow broader access to information, overcoming the limits of time, space, and even cultural values. In light of these profound technological transformations, this study aims to investigate the technological landscape in education, promoting reflections on the use of information and communication technologies (ICTs) and a critical view of their inclusion in schools. The general objective of this article is to discuss the use of ICTs in the teaching and learning process over the past two decades. Specifically, it seeks to describe the application of digital technologies and to demonstrate the need for teacher training for pedagogical practice in relation to ICTs. The findings highlight the role of teachers as facilitators in the construction of students’ knowledge, rather than mere transmitters of information. It is concluded that the use of technologies alone does not entail pedagogical change if they are applied merely as technological support to illustrate lessons. It is essential that they be employed as mediators of learning, contributing to the improvement of the teaching-learning process. The methodology adopted was a qualitative approach through bibliographic review.
Information and communication technologies in teaching and learning
Keywords: Tecnologia da informação e da comunicação; Formação; Praticas pedagógicas; Aprendizagem; Information and Communication Technologies (ICTs); Training; Pedagogical practices; Learning; CIENCIAS HUMANAS